Octopussy [videorecording (DVD)] - Moore, Roger, 1927-2017; Adams, Maud; Jourdan, Louis (Twentieth Century Fox Home Entertainment, 2012)
From a thrilling jet chase, to a climactic countdown, to nuclear disaster, James Bond is back in an electrifying adventure that pushes the limit for nonstop excitement. Roger Moore portrays the immortal action hero, capturing Agent 007's deadly expertise, acerbic wit and overpowering sex appeal as he investigates the murder of a fellow agent who was clutching a priceless Faberge egg at the time of his death.